The Human Side of Artificial Intelligence. - Butkus, Matthew A. (Science & Engineering Ethics, 2020)
Artificial moral agents raise complex ethical questions both in terms of the potential decisions they may make as well as the inputs that create their cognitive architecture. There are multiple differences between human and artificial cognition which create potential barriers for artificial moral agency, at least as understood anthropocentrically and it is unclear that artificial moral agents should emulate human cognition and decision-making. It is conceptually possible for artificial moral agency to emerge that reflects alternative ethical methodologies without creating ontological challenges or existential crises for human moral agents.